2014
DOI: 10.3324/haematol.2013.102897
|View full text |Cite
|
Sign up to set email alerts
|

Severe platelet desialylation in a patient with glycoprotein Ib/IX antibody-mediated immune thrombocytopenia and fatal pulmonary hemorrhage

Abstract: LETTERS TO THE EDITOR Figure 2. (A) P-selectin expression after incubation with patient sera in serial dilutions, expressed as fold change from control sera. (B) Platelet desialylation after incubation with patient sera in serial dilutions. B1-A represents desialylation as measured by flow cytometry detection of fluorescein-conjugated Ricinus Communis Agglutinin I (RCA-1) bound to exposed desialylated galactose residues. (C) Neurominidase (NEU1, red) translocation to the platelet surface (GPIIIa, green) after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Recent findings show that certain anti-GPIba antibodies trigger platelet desialylation, a process that deviates platelet clearance from splenic macrophage Fc receptors to the hepatic AMR, showing that FcgR-independent mechanisms of ITP exist. 102,103 The mechanisms of how anti-GPIba-antibody binding leads to desialylation remain to be established. It is likely that platelets secrete active Neu1 and Neu3 upon antibody binding and/or platelet activation.…”
Section: Immune Platelet Clearancementioning
confidence: 99%
“…Recent findings show that certain anti-GPIba antibodies trigger platelet desialylation, a process that deviates platelet clearance from splenic macrophage Fc receptors to the hepatic AMR, showing that FcgR-independent mechanisms of ITP exist. 102,103 The mechanisms of how anti-GPIba-antibody binding leads to desialylation remain to be established. It is likely that platelets secrete active Neu1 and Neu3 upon antibody binding and/or platelet activation.…”
Section: Immune Platelet Clearancementioning
confidence: 99%
“…However, data show that, in contrast to anti-αIIbβ3-mediated ITP, anti-GPIbα-mediated ITP is often refractory to therapies targeting FcγR pathways or splenectomy. Recent findings show that certain anti-GPIbα-antibodies trigger platelet desialylation, a process that deviates platelet clearance from splenic macrophage Fc-receptors to the liver, likely via the AMR [76], showing that FcγR-independent mechanisms of ITP exist [77]. In this regard, an adult chronic ITP patient with an anti-GPIb-IX autoantibody, who was resistant to corticosteroids, IVIG, recombinant human TPO, rituximab, danazol and vindesine (Eldisine®), has been successfully treated with oseltamivir phosphate, a sialidase inhibitor used to treat influenza [78].…”
Section: Antibody Mediated Platelet Clearancementioning
confidence: 99%
“…Studies in ITP patients and mouse models have suggested an association of anti-GPIb/IX autoantibodies with severe thrombocytopenia [3], as well as with a poor response to either intravenous IgG (IVIG) [4,5] or steroid therapy [6,7]. A recent study in a murine model of ITP suggested that anti-GPIb/IX antibodies may induce platelet desialylation, which can be treated by sialidase inhibition [8,9].…”
Section: Introductionmentioning
confidence: 99%